2017
DOI: 10.1038/icb.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 in the transition of bone marrow progenitors to the thymus

Abstract: Interleukin-7 (IL-7) is essential for the development of T cells in humans and mice where deficiencies in IL-7 signaling result in severe immunodeficiency. T cells require IL-7 at multiple points during development; however, it is unclear when IL-7 is first necessary. We observed that mice with impaired IL-7 signaling had a large reduction in the number of early thymic progenitors (ETPs) while mice that overexpress IL-7 had greatly increased numbers of ETPs. These results indicated that the development of ETPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In thymic T cell development, survival and proliferation were most affected in early thymocytes at DN2 stages in IL-7R-Y449F mice, consistent with a previous report (16,27). Coincidently, development of early thymocytes at ETP to DN2 stages, which expressed higher levels of IL-7Ra in DN thymocyte, was transiently impaired in IL-7R-M452L mice.…”
Section: Discussionsupporting
confidence: 91%
“…In thymic T cell development, survival and proliferation were most affected in early thymocytes at DN2 stages in IL-7R-Y449F mice, consistent with a previous report (16,27). Coincidently, development of early thymocytes at ETP to DN2 stages, which expressed higher levels of IL-7Ra in DN thymocyte, was transiently impaired in IL-7R-M452L mice.…”
Section: Discussionsupporting
confidence: 91%
“…The biological effects of IL-7 on T-cell lymphopoiesis vary for different lineages during the stages of differentiation. Recent studies have shown that the number of early thymic progenitors (ETPs) in mice with impaired IL-7 signaling was significantly decreased, while the number of ETPs in mice with overexpression of IL-7 was greatly increased ( 11 ). The findings indicate that IL-7 can promote the development of ETPs.…”
Section: Il-7/il-7r and T Cellsmentioning
confidence: 99%
“…Bone marrow-residing cells, such as leukocytes, hematopoietic stem cells (HSCs), and stromal cells, secrete cytokines that are important for the development and function of different immune cells. For example, interleukin (IL) -7 is involved in transition of bone marrow progenitor cells to thymus [ 33 ] and bone marrow stromal cell-secreted IL-7 is essential for early B cell development [ 34 , 35 ]. IL-15, secreted by bone marrow stromal cells [ 36 ], can inhibit IL-7 receptor α-chain, which is needed for T cell differentiation [ 37 ].…”
Section: Immuno-oncology and Bonementioning
confidence: 99%